Nenasičene maščobne kisline, fetalni razvoj in ateroskleroza - Kupnik, Dejan (Medicinski razgledi, 2001)
Polyunsaturated fatty acids are a vital part of physiological as well as patophysiological mechanisms in the human body. Their long chained products are a key stone for the development of all fetal tissues especially of the central nervous system and retinas. The process of bonding of hydrogen atoms to fat molecules (fat hydrogenation) is responsible for the structural change of unsaturated fatty acids from cis- into transforms which interfere with the development of long chained polyunsaturated fatty acids within the body of a pregnant woman. This can be a cause for maldevelopment of the prementioned fetal tissues. Omega-3 and omega-6 fatty acids and also their transforms compete for the same encyme systems in the body so it is the balanced intake of the former and avoidance of the later whieh could be a safety factor responsible for lowering the incidence of cerebrovascular and coronary artery disease amongst people. The following essay also explains why the flaxseed is an important source of omega-3 fatty acids for vegetarian pregnant women who do not eat fish.
Keywords: Atherosclerosis; Fetalni razvoj; Maščobne kisline nezasičene; Physiopathology; Lipidna peroksidacija; Fatty acids, unsaturated; Fetal development; Maščobne kisline, omega-3; Nosečnost; Fatty acids, omega-3; human pregnancy; fiziologija; Pregnancy; maščobne kisline; Lipid peroxidation; ateroskleroza; plod; razvoj